The guns at last light : the war in Western Europe, 1944-1945 - Atkinson, Rick (Atkinson, Rick. Liberation trilogy, 2023)
Tells the dramatic story of the titanic battle for Western Europe from D-Day to the thrust to the heart of the Third Reich.